2007
DOI: 10.1097/hjh.0b013e3280119012
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between arterial distensibility and coronary atherosclerosis in angina patients

Abstract: In patients with angina, AO and CA Dist are related to the severity of coronary atherosclerosis, with the relationship being better for alterations in aortic than in carotid mechanical properties. Large elastic artery (and in particular aortic) stiffening can thus be considered as a marker of the severity of coronary atherosclerosis, providing non-invasive obtainable information on the need to proceed with further clinical examinations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 33 publications
2
20
0
Order By: Relevance
“…Thus, both the systolic and diastolic values obtained by the procedure we used can document well-known phenomena such as the age-and blood pressure-related stiffening of large elastic arteries. [1][2][3][4][5][6][7][8][9][10][11][12] And finally, the slope of the carotid diameter-blood pressure changes during systole showed a close relationship with that during diastole. However, over the same blood pressure range, the diameter values of the carotid artery were invariably greater during diastole compared with systole, and so was the slope of the diameterpressure changes.…”
Section: Giannattasio Et Al a New Methods For Carotid Compliance Measumentioning
confidence: 86%
See 1 more Smart Citation
“…Thus, both the systolic and diastolic values obtained by the procedure we used can document well-known phenomena such as the age-and blood pressure-related stiffening of large elastic arteries. [1][2][3][4][5][6][7][8][9][10][11][12] And finally, the slope of the carotid diameter-blood pressure changes during systole showed a close relationship with that during diastole. However, over the same blood pressure range, the diameter values of the carotid artery were invariably greater during diastole compared with systole, and so was the slope of the diameterpressure changes.…”
Section: Giannattasio Et Al a New Methods For Carotid Compliance Measumentioning
confidence: 86%
“…[1][2][3][4][5][6][7][8][9][10][11][12] It has also been shown that this reduction has adverse clinical consequences because large elastic artery stiffening: (1) provides less buffering to the pressor effect of stroke volume and increases the traveling speed of the pressure wave along the arterial tree, with an increase in the reflected wave phenomenon and a systolic blood pressure elevation 13 ; (2) enhances the traumatic effect of intravascular pressure excursions on the vessel wall, thereby favoring atherosclerosis 13 ; and (3) independently increases, at any blood pressure level, the risk of cardiovascular morbid and fatal events. 14 -18 All methods used currently to measure large elastic artery distensibility have limitations.…”
mentioning
confidence: 99%
“…A direct association between functional changes of artery and coronary atherosclerosis has been reported in previous studies. 5,6 However, these studies concluded that this association was stronger for aortic stiffness than carotid arterial stiffness, suggesting that in the larger artery, stiffness could be a significant marker of the severity of coronary atherosclerosis. Within a patient group with preserved LV function in the present study, we did not find a significant relationship between carotid arterial stiffness and the extent of CAD.…”
Section: Discussionmentioning
confidence: 95%
“…7 Thus, a possible explanation for our results may be because this study population excluded patients with multivessel CAD with LV dysfunction accompanied by markedly high carotid arterial stiffness. Furthermore, in the previous studies, 5,6 there was a significant difference in carotid arterial stiffness between patients without CAD and patients with multivessel CAD, but only a modest difference among patients with CAD. Therefore, carotid arterial stiffness might be similar in the limited population comprising only patients with CAD in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation